Hydrochemistry time series at List Ferry Terminal, Sylt, Germany, in 2020 - Svenja Reents; Johannes J Rick; Tatyana Romanova; Marthe Claussen; Petra Kadel; Timm Kress; Birgit Hussel; Karen Helen Wiltshire (PANGAEA, 2024)
The Sylt Roads pelagic time series covers physical and hydrochemical parameters in the Sylt–Rømø bight, Wadden Sea, North Sea. Sea surface temperature (SST), salinity, pH, ammonium, nitrite, nitrate, dissolved (in)organic nitrogen (DIN, DON), silicate, soluble reactive phosphorus (SRP), dissolved organic phosphorus (DOP), chlorophyll a and suspended matter concentrations (SPM) are measured twice a week. These parameters are used to identify long-term changes in the Northern Wadden Sea.
In: Kirstein, Inga Vanessa; Reents, Svenja; Rick, Johannes J; Romanova, Tatyana; Claussen, Marthe; Kadel, Petra; Kress, Timm; van Beusekom, Justus; Hussel, Birgit; Wiltshire, Karen Helen; Boersma, Maarten: Hydrochemistry at time series station Sylt Roads, North Sea since 1973 [dataset publication series]. Alfred Wegener Institute - Biological Institute Helgoland, PANGAEA, https://doi.pangaea.de/10.1594/PANGAEA.986455 (dataset in review)